RAGAM KOSAKATA BAHASA ARAB DALAM PENAMAAN HOTEL DI SURABAYA - Kamal Yusuf; Qomarotul Lail Safrianti; Nailah Rofifah; Adam Nashirullah (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2022)
This study aims to explain the use of various Arabic vocabulary for hotel names in Surabaya. The method used is descriptive-qualitative method. The data was obtained from the android-based hospitality application, namely Booking.com and Traveloka.com. The data is collected, classified, analyzed, then concluded based on linguistic studies, namely linguistic characters, the use of sharia names, and the combination of Arabic with other languages. Based on linguistic characteristics, the names of hotels in Surabaya use singular nouns with a percentage of 89%, while the remaining 5 percent are in the form of verbs and 6% are in the form of Idhofah and plural. The names of hotels that use the word